Assessment of GHG Emission reduction potential from source-separated organic Waste (SOW) management: case study in a higher Educational Institution in Malaysia - Chee, Guan Ng; Sumiani Yusoff, (Universiti Kebangsaan Malaysia, 2015)
In Malaysia, the greenhouse gases (GHGs) emissions reduction via composting of source-separated organic waste (SOW) in municipal solid waste (MSW) has not been assessed. Assessment of GHG emissions reduction via composting of SOW is important as environmental impacts from waste management are waste-specific and local-specific. The study presents the case study for potential carbon reduction via composting of SOW in University of Malaya (UM). In this study, a series of calculations were used to evaluate the GHG emission of different SOW management scenarios. The calculations based on IPCC calculation methods (AM0025) include GHGs emissions from landfilling, fuel consumption in transportation and SOW composting activity. The methods were applied to assess the GHG emissions from five alternative SOW management scenarios in UM. From the baseline scenario (S0), a total of 1,636.18 tCO2e was generated. In conjunction with target of 22% recycling rate, as shown in S1, 14% reduction in potential GHG emission can be achieved. The carbon reduction can be further enhanced by increasing the SOW composting capacity. The net GHG emission for S1, S2, S3 and S4 were 1,399.52, 1,161.29, 857.70 and 1,060.48 tCO2e, respectively. In general, waste diversion for composting proved a significant net GHG emission reduction as shown in S3 (47%), S4 (35%) and S2 (29%). Despite the emission due to direct on-site activity, the significant reduction in methane generation at landfill has reduced the net GHG emission. The emission source of each scenario was studied and analysed.